(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article discusses how to improve the efficiency of working with problem loans in banks. Lending is at the forefront of the functioning of any commercial bank and has always been given a special role. Due to the increased volumes of lending to corporate clients, small businesses and the retail sector, the share of problem debt in banking structures is growing, which may subsequently develop into overdue debt. Consequently, banks are forced to pay great attention to working with problem debt, develop new methods and mechanisms for identifying it, create separate divisions ready to effectively monitor and combat this debt.